2011
DOI: 10.2172/1029436
|View full text |Cite
|
Sign up to set email alerts
|

Effective Permeability Change in Wellbore Cement with Carbon Dioxide Reaction

Abstract: SummaryPortland cement, a common sealing material used in wellbores for geological carbon sequestration, was reacted with carbon dioxide (CO2) in supercritical, gaseous, and aqueous phases at various pressure and temperature conditions to simulate cement-CO 2 reaction along the wellbore from carbon injection depth to the near surface. Hydrated Portland cement columns (14 mm diameter × 90 mm long; water-tocement ratio = 0.33), including additives such as steel coupons and Wallula basalt fragments, were reacted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The air permeability of cement samples was predicted to increase, according to Ghabezloo et al (2009) porosity-dependent equation, from 0.58 to 34.74 mD (34.74×10 -15 m 2 ) after 1 month reaction with CO 2 saturated water at high P-T, as a result of porosity increment from 31 to 45%. The results obtained by Um et al (2011) revealed that the degradation effect of CO 2 saturated groundwater was higher than the effect of cement exposure to supercritical CO 2 , according to X-ray microtomography images carried out on deteriorated specimens. Gasda et al (2004) also referred the potential leakage of CO 2 occurrence on the interface between host rock and cement, cement and casing, cement plug and casing, or through the cement pore space and fracture.…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…The air permeability of cement samples was predicted to increase, according to Ghabezloo et al (2009) porosity-dependent equation, from 0.58 to 34.74 mD (34.74×10 -15 m 2 ) after 1 month reaction with CO 2 saturated water at high P-T, as a result of porosity increment from 31 to 45%. The results obtained by Um et al (2011) revealed that the degradation effect of CO 2 saturated groundwater was higher than the effect of cement exposure to supercritical CO 2 , according to X-ray microtomography images carried out on deteriorated specimens. Gasda et al (2004) also referred the potential leakage of CO 2 occurrence on the interface between host rock and cement, cement and casing, cement plug and casing, or through the cement pore space and fracture.…”
Section: Methodsmentioning
confidence: 93%
“…The porosity and permeability data of the cement class G are herein analyzed under degradation effect of carbon dioxide saturated water and supercritical carbon dioxide, based on an experimental simulation case of a completion inside a gas well. Um et al (2011) conducted an experiment on 14 mm diameter × 90 mm long samples of a class G cement with w/c = 0.33 (water/cement ratio). These specimens were tested under the temperature of 50°C and a pressure of 10 MPa in order to represent the CO 2 injection's temperature and pressure conditions at 1 km of depth, a geothermal gradient of 30°C/km and a pressure gradient of 10.5 MPa/km.…”
Section: Methodsmentioning
confidence: 99%
“…This is because sandstone is primarily composed of silica quartz, which reacts at rates that are orders of magnitude lower than cement. Due to the more than 4 orders of magnitude in permeability contrast between the sandstone (100 mD, reported by the provider) and cement zone (4-8 µD, Um et al, 2011), CO 2 -brine primarily flowed through the more permeable sandstone zone. As a result, the acidic brine degraded the cement at the interface of sandstone and cement zone.…”
Section: Visual Evidence Of Core Sample Alterationsmentioning
confidence: 90%
“…The effective porosity of the sandstone-cement core and limestone-cement core was measured to be 15.4% and 13.9%, respectively. According to literature, an unreacted cement column with water-to-cement ratio of 0.38 has a total porosity of 31% and an effective permeability of 4~8 µD (Um et al, 2011). These core plugs were then dried overnight in an oven before the core flooding experiments.…”
Section: Sample Preparation and Flow-through Experimentsmentioning
confidence: 99%
See 1 more Smart Citation